Carrier‐based pulse‐width modulation control strategy of five‐phase six‐bridge indirect matrix converter under unbalanced load. Issue 14 (1st November 2017) - Wang, Rutian; Wang, Weiquan; Liu, Ruitong; Zhang, Jiawei; Mu, Xingjun
Abstract : To solve the problem that three‐to‐five‐phase matrix converter (MC) cannot supply symmetrical voltages to unbalanced loads, a topology of five‐phase six‐bridge indirect MC and a carrier‐based pulse‐width modulation (PWM) method are proposed. A midline bridge is added to the neutral point of five‐phase loads in inverter stage. The neutral point voltage is analysed and derived by space vector PWM (SVPWM) method for calculating the duty ratio of midline bridge. Calculations of other five‐phase bridge duty ratios of SVPWM method remain unchanged. All of the duty ratios are used to calculate modulation waves of rectifier stage and inverter stage. Driving signals of two‐stage power switches are generated by comparing the modulation waves with a carrier, which are used to control the neutral voltage as corresponding zero‐sequence voltage. Therefore, five symmetrical output voltage sinusoids are obtained under both balanced and unbalanced loads. Finally, simulation and experimental results are provided to verify the feasibility and validity of the proposed method.